Glycol ethers and semen quality: a cross-sectional study among male workers in the Paris Municipality. Issue 7 (1st March 2007) - Multigner, L; Ben Brik, E; Arnaud, I; Haguenoer, J M; Jouannet, P; Auger, J; Eustache, F
Abstract : Objectives: Apparent increases in human male reproductive disorders, including low sperm production, may have occurred because of increased chemical exposure. Various glycol ether-based solvents have pronounced adverse effects on sperm production and male fertility in laboratory animals. The authors investigated the effects of past and current exposure to glycol ether-containing products on semen quality and reproductive hormones among men employed by the Paris Municipality. Methods: Between 2000 and 2001 the authors recruited 109 men who gave semen, blood and urine samples and underwent an andrological examination. Information on lifestyle, occupation, exposure and medical history was obtained by interview. According to their job and chemical products used during the period 1990–2000, men were classified as either occupationally exposed or non-exposed. Current exposure levels to glycol ethers at the time of the study were evaluated by biological monitoring of six urinary metabolites. Results: Previous exposure to glycol ethers was associated with an increased risk for sperm concentration, for rapid progressive motility and for morphologically normal sperm below the World Health Organization semen reference values. No effect of previous glycol ether exposure on hormones levels was observed. By contrast, current glycol ether exposure levels were low and not correlated with either seminal quality or hormone levels. Conclusions: This study suggests that most glycol ethers currently used do not impact on human semen characteristics. Those that were more prevalent from the 1960s until recently may have long lasting negative effects on human semen quality.